2023
DOI: 10.1016/j.rpsm.2021.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Association between perceived discrimination and mental health outcomes among health workers during the initial COVID-19 outbreak

Abstract: Background During the initial COVID-19 outbreak, health systems faced unprecedented organizational stress. Meanwhile, reports of episodes of discrimination and violence towards healthcare workers increased globally. This study explores the association between perceived discrimination and mental health outcomes in a large sample of healthcare workers in Spain. Materials and methods Healthcare workers from inpatient and outpatient facilities ( N … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 15 publications
1
13
0
1
Order By: Relevance
“…In a few weeks, they went from heroes to negligent professionals in the eyes of many persons, while a number of lawyers and prosecutors started to put their decisions and treatment choices under judiciary scrutiny ( 16 ). Although studies from other countries have shown the negative impact of stigma and violence related to COVID-19 on HCWs' mental wellbeing ( 17 , 18 ), these factors have been neglected in previous research conducted in Italy. In the present paper, we used a large national sample of Italian HCWs to examine whether their mental wellbeing during the challenging reopening phase after lockdown was related to 1) individual-level factors such as stigma and violence against HCWs, and 2) workplace-level factors related to COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…In a few weeks, they went from heroes to negligent professionals in the eyes of many persons, while a number of lawyers and prosecutors started to put their decisions and treatment choices under judiciary scrutiny ( 16 ). Although studies from other countries have shown the negative impact of stigma and violence related to COVID-19 on HCWs' mental wellbeing ( 17 , 18 ), these factors have been neglected in previous research conducted in Italy. In the present paper, we used a large national sample of Italian HCWs to examine whether their mental wellbeing during the challenging reopening phase after lockdown was related to 1) individual-level factors such as stigma and violence against HCWs, and 2) workplace-level factors related to COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, it has been reported that between 28-38% suffered anxiety, 15-36 % from depression and 25-46% from sleep problems ( Luo et al, 2020 ; Pappa et al, 2020 ; Rodriguez-Menéndez et al, 2021 ; Wu et al, 2021 ). Moreover, a significant proportion of HCW facing COVID-19 pandemic have experienced discrimination and/or stigmatization which has been demonstrated to impact negatively on the mental health status of HCW ( Mediavilla et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Multiple social and economic consequences have already been reported (e.g., spiking unemployment rates), while others are expected to occur in the following months, and they have been increasing social divides and inequalities across the world [ 6 ]. There has also been a diversity of responses to HCWs, ranging from public cheering and gratitude to stigma and assault [ 7 ], especially in some low-and-middle-income countries (LIMCs).…”
Section: Introductionmentioning
confidence: 99%
“…These may lead to moral injury [ 15 ], which may be internalized and compound the acute stress of working during a pandemic [ 16 , 17 ]. Moreover, social exposures such as stigma and harassment toward HCWs may worsen effects on mental health, though these have not been carefully studied yet [ 7 ]. To assess the risk and predictors of mental health disorders among HCWs during COVID-19 individual factors must be accounted for, as well as the potential impact of workplace and social conditions and policies, which are potentially modifiable conditions.…”
Section: Introductionmentioning
confidence: 99%